RNA-Seq Whole Transcriptome Analysis of Bovine Mammary Epithelial Cells in Response to Intracellular Staphylococcus aureus - Wang, Xiaozhou; Su, Feng; Yu, Xiaohui; Geng, Na; Li, Liping; Wang, Run; Zhang, Meihua; Liu, Jianzhu; Liu, Yongxia; Han, Bo (Frontiers in Veterinary Science, 2020)
Staphylococcus aureus (S.aureus) is a common mastitis pathogen that is widespread in the natural environment of the dairy farms and is capable of invading mammary epithelial cells making treatment of the disease difficult. However, the mechanism of bovine mammary epithelial cells in response to S.aureus invasion remains elusive. In this study, transcriptomic analysis and bioinformatics tools were applied in order to explore the differentially expressed RNAs in bovine mammary epithelial cells between control group and S.aureus-treated group. A total of 259 differentially expressed mRNAs (DEmRNAs), 27 differentially expressed microRNAs (DEmiRNAs), and 21 differentially expressed lncRNAs (DElncRNAs) were found, which mainly enriched in inflammatory response, immune response, endocytosis, cytokine-cytokine receptor interaction. Finally, qRT-PCR was used to analyze the quality of RNA-seq results. This study discovered candidate DEmRNAs, DElncRNAs and DEmiRNAs and pathways involved in bovine mammary epithelial cells defense against S.aureus. The findings of this study provide valuable insights into the biological responses of bovine mammary epithelial cells during intracellular infection of S.aureus.